Rare-earth-free white emitting Ba2TiP2O9 phosphor: revealing its crystal structure and photoluminescence properties. Issue 28 (29th June 2016) - Hasegawa, Takuya; Kim, Sun Woog; Kamei, Shinnosuke; Ishigaki, Tadashi; Uematsu, Kazuyoshi; Ohmi, Koutoku; Toda, Kenji; Sato, Mineo
Abstract : Crystal structure of a Ba2 TiP2 O9 phosphor has been revealed by Rietveld refinement, it has monoclinic structure which consists of PO4 tetrahedra and TiO5 pyramidal polyhedra connected to form a chain structure along the c -axis. Abstract : A high intensity bluish-white emitting Ba2 TiP2 O9 phosphor was synthesized by a conventional solid-state reaction method and the precise crystal structure was investigated for the first time by Rietveld refinement analysis. Ba2 TiP2 O9 has a monoclinic crystal structure with a space group C 2/ c (no. 15), which is built out of PO4 tetrahedra and TiO5 pyramidal polyhedra connected to form a chain structure along the c -axis. The emission of Ba2 TiP2 O9 is due to a charge transfer transition between Ti 4+ –O 2− in the pyramidal TiO5 . The obtained Ba2 TiP2 O9 was excited efficiently by UV and VUV and displayed a bright bluish-white luminescence.